Academic writing : a handbook for international students - Bailey, Stephen, 1947- (London : Routledge, 2025)
"The new sixth edition of this popular book has been written to help international students succeed in writing essays and reports for their English-language academic courses. Thoroughly revised and updated in a streamlined format making it even easier for students and teachers to use, Academic Writing: A Handbook for International Students is designed to let readers find the support they need easily, both in the classroom and for self-study. The book consists of three parts, comprising a total of 28 units: The Writing Process and Writing Skills; Elements of Writing; and Writing Models. The first part explains and practises every stage of essay writing, from choosing the best sources, reading and note-making, through to referencing and proofreading. These stages are supported by relevant explanations of critical writing skills, so that, for instance, finding synonyms is linked with paraphrasing and summarising. The second part explains critical issues such as using numbers and punctuation, and is organised alphabetically, while the third part provides models for common components of student writing such as case studies and reports. All units are fully cross-referenced and can be taught in conjunction with each other or used for self-study or reference. A progress check at the end of each part allows students to self-assess their learning, and a complete set of answers to the practices exercises is included. Additional features of the book include: Use of authentic academic texts from a wide range of disciplines Designed for self-study as well as classroom use Useful at both undergraduate and postgraduate level Fully updated, with sections on using AI and exploring electronic sources Access to the free interactive website which includes a full set of teaching notes as well as more challenging exercises, revision material and links to other sources. All international students wanting to maximise their academic potential will find this practical and easy-to-use book an invaluable guide to writing in English for their degree courses"--
Includes bibliographical references and index.
Keywords: English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Textbooks for foreign speakers; Academic writing -- Handbooks, manuals, etc